Histone H2A/H2B chaperones: from molecules to chromatin‐based functions in plant growth and development. (8th April 2015) - Zhou, Wangbin; Zhu, Yan; Dong, Aiwu; Shen, Wen‐Hui
Summary Nucleosomal core histones (H2A, H2B, H3 and H4) must be assembled, replaced or exchanged to preserve or modify chromatin organization and function according to cellular needs. Histone chaperones escort histones, and play key functions during nucleosome assembly/disassembly and in nucleosome structure configuration. Because of their location at the periphery of nucleosome, histone H2A–H2B dimers are remarkably dynamic. Here we focus on plant histone H2A/H2B chaperones, particularly members of the NUCLEOSOME ASSEMBLY PROTEIN‐1 (NAP1) and FACILITATES CHROMATIN TRANSCRIPTION (FACT) families, discussing their molecular features, properties, regulation and function. Covalent histone modifications (e.g. ubiquitination, phosphorylation, methylation, acetylation) and H2A variants (H2A.Z, H2A.X and H2A.W) are also discussed in view of their crucial importance in modulating nucleosome organization and function. We further discuss roles of NAP1 and FACT in chromatin‐based processes, such as transcription, DNA replication and repair. Specific functions of NAP1 and FACT are evident when their roles are considered with respect to regulation of plant growth and development and in plant responses to environmental stresses. Future major challenges remain in order to define in more detail the overlapping and specific roles of various members of the NAP1 family as well as differences and similarities between NAP1 and FACT family members, and to identify and characterize their partners as well as new families of chaperones to understand histone variant incorporation and chromatin target specificity.